PERANCANGAN SISTEM INFORMASI LAPORAN HASIL PRODUKSI DEPARTEMEN DECORATION PADA PT. LUNG CHEONG BROTHER INDUSTRIAL KRAGILAN KABUPATEN SERANG - Ely Nuryani; Yuyun Rosmiati (Jurnal Ilmiah Sains dan Teknologi, 2019)
PT. Lung Cheong Brother Industrial only produces small children's toys. Production results Inputs and outputs always vary every day, so there is a need for data to determine the profits or profits of a company. Data in the form of production can be arranged neatly in a report. Problems that are often found at PT. Lung Cheong Brother industrial is a form of production report that is still made manually, so it requires a relatively long time, then the presentation and preparation of production data is not neatly organized, consequently it will make it difficult to find data, requires considerable costs because it must provide tools adequate writing, production reports will be difficult to understand and difficult to understand the intent and purpose, and frequent occurrence of data in the reports made. The research method used includes library research by collecting data obtained from several guidebooks or library books as references that are appropriate to the problem and field research based on the results of the research object directly. The aim to be achieved in this study is to find out how to record production results can be done in real time, to find out how the production reports are neatly arranged so that they can search data quickly and precisely, and to find out the problems faced by PT. Lung Cheong Brother industrial in producing production reports.